Preliminary Assessment of Fauna Species Diversity in Ipinu Igede Community Range Forest in Oju Local Government of Benue State, Nigeria (2018)
Background and Objectives: Appraisal of fauna species which form an integral part of range ecology, in rangeland based protected areas is necessary before any meaningful conservation work can commence. This study was aimed at assessing the composition of fauna species in the community forest. Methodology: Animal species were enumerated through direct on-site using four transects line of 2.0 km by 10 m broad distributed randomly, field observation and indirect indices. Data were analyzed using descriptive statistics (table, figures and plates). Results: Fifty-six species of wild animals from 40 families were observed in the study area. There were 21 species of mammals from 15 families, 6 species of reptiles from 6 families and 29 species of birds from 19 families. A total of 1,419 sightings were recorded. The most abundant animal species found in the area were Epixerus ebii, Eidolon helvum, Chlorocebus tantalus, Papio anubis, Philothemus irregularis, Musophaga violacea, Numidia meleagris and Francolinus bicalcaratus. The status of most mammals was Low risk-conservation dependent as applicable to reptiles. All the birds are known to breed in the reserve. Transect C had the highest diversity index (0.0130) and transect A had the lowest animal diversity index (0.0061) but with the highest species count of thirty six (36) and individual animal species sighted (454). Conclusions: The community forest support unique fauna species making it significant in terms of conservation and scientific interest and has to be protected through conservation awareness and community participation to conserve the current state and enhanced its range productivity.